EXPRESSION OF THE CONCEPT OF “PATRIOTISM” IN THE RUSSIAN-LANGUAGE MEDIA (Scientific journal of the Fergana State University, 2024)
This research delves into the multifaceted concept of "patriotism" and its portrayal in media discourse. The study aims to explore how media texts construct and manipulate the notion of patriotism in the context of Russian national identity. The methods employed include an examination of cognitive models, intertextuality, and the contrasting images utilized in media narratives. The results highlight the complexity of patriotism, which is presented as both a deeply positive emotion and a fusion of various social sentiments and value orientations. This research elucidates the pivotal role of media in constructing and disseminating notions of patriotism within the Russian context. It sheds light on how these portrayals can range from inspiring national pride to perpetuating negative stereotypes, depending on the methods employed in the media narrative. Understanding these dynamics is crucial in comprehending the complexities of national identity and the influence of media in shaping public perception.